Income Gradient in Renal Disease Mortality in the United States - Assari, Shervin; Lankarani, Maryam Moghani (Frontiers in Medicine, 2017)
Background: Distribution of kidney disease and associated mortality follow a social gradient. Role of intermediate and proximal factors that explain such social gradient is, however, unknown. Objectives: Using a nationally representative data in the U.S., this study was conducted to investigate mediating effect of intermediate (chronic medical diseases) and proximal (health behaviors) factors on the effects of socioeconomic status (SES) on renal disease mortality. Patients and Methods: Americans’ Changing Lives Study (ACL), 1986 – 2011, is a 25-year nationally representative prospective cohort study. The ACL followed 3,361 adults (1,156 Blacks, 2,205 Whites) for up to 25 years. Socioeconomic factors (income, education, and unemployment) were the main predictors of interest. Death due to renal disease was the main outcome. Health behaviors (smoking, drinking, and exercise) and medical risk factors (diabetes, hypertension, and obesity) were the mediators. Cox proportional hazards models were used for data analysis. Results: Low income was a risk factor for death due to renal disease over the follow up period. Although health behaviors and medical risk factors at baseline were also predictor of the outcome, health behaviors and medical risk factors failed to explain the effect of income on death due to renal disease. Conclusions: Socioeconomic disparities in the United States cause disparities in renal disease mortality, however, such differences are not due to health behaviors (smoking and drinking) and medical risk factors (hypertension and diabetes). To reduce disparities in renal disease mortality in the United States, policies should go beyond health behaviors and medical risk factors. While programs should help low income individuals maintain exercise and avoid smoking, reduction of income disparities should be regarded as a main strategy for reduction of disparities in renal disease mortality.